Handbook of Media Branding - Siegert, Gabriele.; Siegert, Gabriele.; Förster, Kati.; Förster, Kati.; Chan-Olmsted, Sylvia M.; Chan-Olmsted, Sylvia M.; Ots, Mart.; Ots, Mart. (Springer International Publishing : Imprint: Springer, 2015)
This comprehensive handbook critically addresses current issues and achievements in the field of media branding. By discussing media branding from different viewpoints, disciplines and research traditions, this book offers fresh perspectives and identifies areas of interest for further research. The authors highlight the peculiarities of this field and reveal links and commonalities with other areas of study within communication science. The chapters address different research areas, such as society-, content-, management-, audience- as well as advertising aspects of media brands. This handbook thus brings together contributions from different areas making it a valuable resource for researchers and experts from industry interested in media branding.